2023
DOI: 10.1097/j.jcrs.0000000000001225
|View full text |Cite
|
Sign up to set email alerts
|

Topical analgesics for acute corneal pain: current options and emerging therapeutics

Abstract: Acute corneal pain is a common complaint that causes significant distress to patients and continues to challenge therapeutic avenues for pain management. Current topical treatment options have marked limitations in terms of both efficacy and safety, thus often prompting the adjunctive use of systemic analgesics, including opioids. In general, there have not been extensive advancements in pharmacologic options for the management of corneal pain over the past several decades. Despite this, multiple promising the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 70 publications
(142 reference statements)
0
1
0
Order By: Relevance
“…Topical administration of opioids might be more effective at avoiding potential side effects. A few studies have revealed that topical opioids reduced pain scores and increased rate of epithelial healing post-photorefractive keratectomy without deleterious effects [64,65]. A phase I study indicated the tolerability to escalating doses of topical naltrexone (1-4 eye drops at dosages up to 50 µM) in healthy individuals [66].…”
Section: Discussionmentioning
confidence: 99%
“…Topical administration of opioids might be more effective at avoiding potential side effects. A few studies have revealed that topical opioids reduced pain scores and increased rate of epithelial healing post-photorefractive keratectomy without deleterious effects [64,65]. A phase I study indicated the tolerability to escalating doses of topical naltrexone (1-4 eye drops at dosages up to 50 µM) in healthy individuals [66].…”
Section: Discussionmentioning
confidence: 99%